EFEKTIVITAS PROGRAM CENGKRAMAN MATA ELANG DALAM MENCEGAH KASUS STUNTING DI KABUPATEN DEMAK - Wahsyati, Anis; Rostyaningsih, Dewi; Warsono, Hardi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research aims to analyze the effectiveness of the Cengkraman Mata Elang program in preventing stunting cases in Demak Regency and explain the supporting and inhibiting factors. This research uses a qualitative approach with a descriptive research model. Data collection techniques include interviews and documentation. The effectiveness of the Cengkraman Mata Elang program is measured through four criteria including program socialization, achievement of objectives, accuracy of implementation, and program monitoring. The research results show that the Cengkraman Mata Elang program to prevent stunting has not been effective. The criteria for program socialization and achievement of goals have not been effective. Program socialization has not been effective because cadres as targets and implementers of the Cengkraman Mata Elang program have low awareness in inputting and reporting the condition of pregnant women and toddlers; and cadre loyalty and professionalism are also still low. The criteria for achieving the goal are not yet effective because the change in stunting cases in Demak Regency has not yet reached the national reduction target and health workers as application users still experience technical obstacles that hamper their performance in preventing and dealing with stunting. Supporting factors include the availability of a special budget for the Cengkraman Mata Elang program as well as specifically for preventing and handling stunting; support for stunting prevention and management from various OPDs in Demak Regency; condition and availability of complete infrastructure for the Cengkraman Mata Elang application; and there is intense assistance to the target group. The inhibiting factor is the absence of budget assistance for cadres as program implementers. Suggestions that can be given are the need to provide a survey questionnaire which is filled out by cadres every month, the need to provide a policy that cadres are required to report data on the condition of pregnant women and toddlers, the need for cooperation with the Civil Registry Office to synchronize NIK and personal data, the need for system updates in the form of automatic data recording, and the need to provide incentives and rewards to cadres.